Effectiveness of antihypertensive therapy based on arresting of specific features in psychosomatic patients - G. A. Usenko; A. G. Usenko; D. V. Vasendin; S. V. Ivanov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
In contrast to the empirical therapy, 18month antihypertensive therapy based on administration of adrenoblockers to the patients with the sympathetic division activity (cholerics and sanguinics), and the angiotensinconverting enzyme activity in the patients with renninangiotensinaldosterone system due parasimpatikotonii (phlegmatics and melancholics) combined with the alignment of values of the studied parameters with those in healthy individuals of the same temperament.